Effect of socio-economic characteristics of hotel guests on acceptability of roasted meat (suya) as hotel menu in Ogun State, Nigeria (2016)
Suya is meat prepared and cooked by roasting on glowing charcoal fire. It has become a popular mass consumer meat snack in Nigeria. It is usually sold along the streets, in club houses, at picnics, state parties, restaurants and around hotel buildings. As a mass consumer fast food, its consumption cut-across ethnic, religious, sex and socio-economic background but its acceptability as hotel menu in Ogun State is not certain, hence this study. Purposive sampling technique was used to select the respondents from zones in Ogun State viz: Egba, Ijebu, Remo and Yewa. Two Communities were selected from each zone while one popular hotel in each community was selected. A total of three hundred and sixty respondents were interviewed, the results revealed that 240 of hotel guests (66.7%) showed indifferent attitudes to acceptability, of roasted meat (Suya) as hotel food item, while 120 out of360 questionnaire respondents (33.3%) accepted Suya as hotel food item. There was significant relationship established between socio-economic status and preference for Suya as hotel menu in Ogun State 41.00.005).